IMMU-07. IMMUNOLOGIC TARGETING OF DIPG WITH H3K27M ENCODING RNA-NANOPARTICLES. (23rd April 2019) - McGuiness, James; Mendez-Gomez, Hector; Stover, Brian; Weidert, Frances; Mitchell, Duane; Sayour, Elias
Abstract: BACKGROUND: Diffuse Intrinsic Pontine Glioma (DIPG) remains uniformly recalcitrant and thus necessitates development of novel targeted therapies. The histone mutation in H3K27M is conserved in the preponderance of DIPG patients and may be exploited as a neoepitope for cancer immunotherapy. We have developed a novel treatment platform, which leverages the use of clinically translatable nanoparticles (NPs) combined with H3K27M mRNA neoantigens for in vivo activation of dendritic cells and generation of DIPG specific T cells. OBJECTIVE/METHODS: Since neoantigens have been shown to mediate immunologic response through MHC class II, we sought to identify MHCII restricted epitopes spanning the H3.1K27M junction for development of RNA-NP vaccines against DIPG. RESULTS: We identified MHCII restricted H3.1K27M epitopes not present in the wild-type sequence. We constructed a 25-mer sequence (75 amino acids) spanning the range of epitopes, before cloning it into our custom pGEM-4z plasmid containing a poly A tail and 5' UTR with a T7 promoter for amplification of MHC-II restricted H3.1K27M mRNA. We complexed this RNA with our custom NP formulation and investigated its immunogenicity in C57Bl/6 mice. Unlike MHC-I restricted epitopes (i.e. OVAlbumin's SINFEKL epitope), MHC-II restricted H3K27M epitopes elicited significant increases in activated CD4 and CD8 central memory T cells. We demonstrate that this central memory phenotype correlates with anti-tumor efficacy and long-term survival outcomes in murine tumor models. CONCLUSION: RNA-NPs can be made readily available for all DIPG patients (and not only HLA specific haplotypes) providing a renewable antigen resource that can be used to continuously vaccinate patients for months/years after diagnosis. Herein, we identify MHCII restricted H3.1K27M epitopes for activation of immunologic central memory necessary for long-lived anti-tumor efficacy.